Assessment of atmospheric dynamics in the high Andean region of Chimborazo Province. Evaluación de la dinámica atmosférica en la zona alto andina Provincia-Chimborazo - Lara-Sinaluisa, Jorge Milton; Martínez-Nogales, Juan Manuel; Morales-Rovalino, Vanessa Fernanda; Lara-Avalos, Sandra Daniela; Haro-Velasteguí, Arquímides Xavier (International Journal of Aquatic Research and Environmental Studies, 2026)
The study evaluates the dynamic conditions of the lower atmosphere in the high Andean zone of the province of Chimborazo, using the Van Ulden-Holtslag model, adapted to the particular altitude and temperature conditions of the area, as well as to the specific soil conditions. Data obtained from the Atillo, Tixán, and Chocaví weather stations, collected hourly between 2018 and 2021, were used for the variables: humidity, pressure, radiation, temperature, and wind speed. In addition, data such as roughness, albedo, air density, Bowen index, and runoff constant were collected. Applying the Van Ulden-Holtslag model, heat fluxes, friction velocity, and, fundamentally, the Obukhov length were calculated to define stability levels according to the Pasquill classification. The results show that, for the years analyzed, at the weather stations (Atillo, Tixán, and Chocaví), the extremely stable (EE) class prevailed in its entirety, with only 2019 at the Tixán and Chocaví stations, as well as 2020 at the latter station, showing a prevalence of neutral (N), moderately stable (ME), and moderately unstable (MI) stability classes, respectively. Atmospheric stability models are essential for predicting the dispersion of atmospheric pollutants and improving public health.